Philanthropic Foundations' Discourse and Nursing's Future: Part I: History and Agency. (6th April 2023) - Kneipp, Shawn M.; Drevdahl, Denise J.; Canales, Mary K.
Abstract : In this article, we examine external agents' effect on nursing's professional evolution and the consequences for the discipline's collective agency, social contract, and self-regulation. Situated within Foucault's theories of power, we review how the power of organizations reaches into the fabric of everyday life and explore how philanthropic foundations have influenced a diverse array of disciplines, including nursing. Through a genealogic lens, we examine nursing history and professionalization and conclude with concerns surrounding nursing's exercise of its collective agency during one of the most significant, discipline-shaping activities of modern times—Robert Wood Johnson Foundation's Future of Nursing initiatives.